2013
DOI: 10.1007/s11517-013-1078-x
|View full text |Cite
|
Sign up to set email alerts
|

The remodeling of alveolar bone supporting the mandibular first molar with different levels of periodontal attachment

Abstract: The objective of this study was to investigate alveolar bone remodeling of the mandibular first molar with differing levels of periodontal attachment under mastication loading. Three-dimensional finite element models of the mandibular first molar with differing levels of periodontal attachment were established. The stress distributions and bone density changes were analyzed under mastication loading to simulate the remodeling process of mandibular bone based on the theory of strain energy density. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…Zhao et al . had built a FE model of lower first molar including tooth, periodontal membrane, part of cortical bone and trabecular bone, and applied a 420 N vertical force on the occlusal surface of tooth model. The results showed that the alveolar areas in buccal and lingual ridges and root apex regions experienced higher stresses when the tooth was loaded.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al . had built a FE model of lower first molar including tooth, periodontal membrane, part of cortical bone and trabecular bone, and applied a 420 N vertical force on the occlusal surface of tooth model. The results showed that the alveolar areas in buccal and lingual ridges and root apex regions experienced higher stresses when the tooth was loaded.…”
Section: Discussionmentioning
confidence: 99%
“…As such it is constantly subjected to external mechanical stresses that cause its continuous remodeling and resorption. 1 Since spontaneous regeneration does not occur in alveolar bone, damage caused by trauma or periodontitis generally requires surgical interventions that may result in tooth loss and the need for bone grafting, accompanied by its associated risks (reviewed in Ref. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…94 Under such differences in load, the supporting alveolar and maxillary bone structures undergo load-dependent bone remodeling with bone resorption seen under extreme loading. 95 Preferential binding of labeled ZOL to certain anatomical bone sites was recapitulated in animal models with distinct areas of the posterior mandible (ascending ramus and mandibular molar alveolar bone) demonstrating increased fluorescence labeling. 96 Similar anatomical differences were also seen in the femur with more labeling in the proximal area of primary spongiosa than distal region, which may explain the increased risk of avascular necrosis of the femoral head.…”
Section: Mechanism Of Actionmentioning
confidence: 92%